Cold‐shock based method to induce the discharge of extrusomes in ciliated protists and its efficiency. (16th September 2015) - Buonanno, Federico; Ortenzi, Claudio
Abstract : Extrusomes are ejectable organelles in protists, which are able to discharge their contents to the outside of the cell in response to external stimuli. It is known that a large number of extrusomes functions as organelles for offense or defense in predator‐prey interactions among protists and/or microinvertebrates. To date, the main approach to study these interactions was to compare artificially‐induced extrusome‐deficient cells with normal cells as prey for predators. Commonly applied methods to obtain extrusome‐deficient cells use external chemicals, which could alter the viability of cells and/or interfere with the subsequent analysis of the substances (secondary metabolites) contained in the extrusomes. The cold‐shock based method here presented has proven to be effective to remove different kinds of extrusomes from several protist species without harming the treated cells and without adding external reagents. This method could be also useful to simplify the related analysis of the chemical nature of the secreted secondary metabolites.